Bis[(4-chlorobenzyl)triphenylphosphonium] tetrachloridozincate(II) trihydrate - Tan, K.W.; Maah, M.J.; Ng, S.W. (International Union of Crystallography, 2010)
The crystal structure of the title compound, (C(25)H(21)ClP)(2)[ZnCl(4)] center dot 3H(2)O, consists of tetrahedral phosphonium cations and tetrahedral zincate anions; the water molecules form weak hydrogen bonds to the anions. Two of the water molecules are disordered over three sites in a 0.68:0.55:0.77 ratio.